Zirconium nanosheet with confinement effect, preparation method and application
By preparing zirconium nanosheets with confinement effect (T-ZrNs) and controlling the pH value, the problems of dispersion stability and penetration efficiency of zirconium nanosheets in leather tanning were solved, achieving uniform distribution and multi-point cross-linking of zirconium ions, thereby improving the tanning effect and the shrinkage temperature of the tanned leather.
Patent Information
- Application Number
- CN202510898899.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-01
- Publication Date
- 2025-10-28
AI Technical Summary
Traditional zirconium nanosheets suffer from poor dispersion stability, high hydrolysis sensitivity, and low penetration efficiency during leather tanning, resulting in uneven tanning effects.
Zirconium nanosheets (T-ZrNs) with confinement effect were prepared by reacting zirconium salt, carboxyl-containing polydentate ligands and acetic acid modulator in N,N-dimethylformamide, followed by ultrasonic dispersion and high-temperature treatment. The pH value was controlled during the leather tanning process to achieve uniform distribution and multi-point cross-linking of zirconium ions.
It improves the penetration performance and tanning effect of zirconium ions, avoids the phenomena of "surface over-tanning" and "raw core", and increases the shrinkage temperature of the tanned leather.
Smart Images

Figure CN120839077A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of zirconium nanosheet preparation and application, specifically involving zirconium nanosheets with confinement effect, methods for preparing zirconium nanosheets with confinement effect, and their applications. Background Technology
[0002] Leather processing involves a series of processing steps on animal hide collagen fibers to produce shoes, clothing, bags, and other products with practical value, thus achieving the effective utilization of resources. Tanning is a key step in the leather-making process, involving the chemical modification of raw hides using tanning agents to transform them into leather. Chrome tanning agents impart excellent tanning properties to leather and are widely used. However, chrome tanning agents are poorly absorbed, and Cr(III) in chrome tanning agents can be converted to Cr(VI) under certain conditions. Cr(VI) is highly toxic and can harm human health and the environment. Therefore, the development of environmentally friendly chrome-free tanning agents is imperative.
[0003] Zirconium tanning agents are a class of inorganic metal tanning agents with zirconium salts as the main component. Zirconium salts such as zirconium chloride or zirconium sulfate are commonly used as zirconium tanning agents in leather making. Zirconium tanning agents produce leather with good fullness, high shrinkage temperature, and good abrasion resistance, making them the most promising non-chromium metal tanning agents to replace chromium tanning agents. However, the hydrolysis and polymerization process of zirconium salts is relatively fast, easily reacting quickly on the surface of the raw leather, clogging pores, and preventing further penetration into the collagen fibers, leading to problems such as "over-tanning on the surface" and "raw core" in the raw leather.
[0004] Zirconium nanosheets (ZrNs) are two-dimensional nanosheet materials with a thickness at the nanometer level, composed of zirconium salts and carboxyl-containing polydentate ligands linked by coordination bonds. Compared with traditional bulk materials, the two-dimensional nanosheet structure of ZrNs restricts the diffusion of zirconium ions, resulting in a strong spatial confinement effect. In addition, ZrNs have the characteristics of tunable structure, small size, and strong stability. Based on the coordination interaction between zirconium salts and organic linkers, researchers have synthesized ultrathin zirconium nanosheets containing periodic structural units using a pseudo-assembly-disassembly strategy. The ultrathin size endows the zirconium nanosheets with abundant active sites, and the coordination structure effectively coordinates the zirconium active sites in the sheet, achieving a stable arrangement of zirconium ions (Small, 2018, 14(16), 1703929).
[0005] The spatial confinement effect of ZrNs can be used to achieve the random migration of Zr ions / clusters and reduce the diffusion activation energy of single atoms (Shifa, TA; Vomiero, A. 2019, 9(40),1902307), which is expected to solve the problem of difficult control of zirconium ion hydrolysis and aggregation in traditional zirconium tanning. However, ZrNs as a leather tanning agent faces three major problems in application: poor dispersion stability (easy to aggregate in acidic / high-salt environments), strong hydrolysis sensitivity (rapidly generating inert colloids at pH>3, reducing active zirconium binding sites), and low penetration efficiency (large-sized nanosheets are difficult to penetrate into the dermis). These problems lead to uneven tanning effect and limited practical application, which urgently need to be solved through surface modification and process optimization. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing zirconium nanosheets with confinement effect, which solves the problems of poor dispersion stability and high hydrolysis sensitivity of common zirconium nanosheets.
[0007] Another objective of this invention is to provide zirconium nanosheets with confinement effects.
[0008] The present invention also aims to provide the application of zirconium nanosheets with confinement effect, which solves the problem of difficulty in controlling the hydrolysis and polymerization process of zirconium ions in the traditional zirconium tanning process.
[0009] The first technical solution adopted in this invention is a method for preparing zirconium nanosheets with confinement effect. The method involves dissolving zirconium salt, a carboxyl-containing polydentate ligand, and an acetic acid modifier separately in N,N-dimethylformamide, ultrasonically dispersing the solutions, and then transferring them to a reaction vessel for heating and reaction to obtain T-ZrNs. The specific operation steps are as follows: Step 1: Add zirconium salt, carboxyl-containing polydentate ligand, and acetic acid modifier to N,N-dimethylformamide, wherein the ratio of the series of carboxyl-containing polydentate ligands to acetic acid modifier is 0.6g~1.4g:1ml. Disperse the mixture by ultrasonication at room temperature, transfer it to a polytetrafluoroethylene high-pressure reactor, heat it to 120℃~130℃, and react for 30~40min. Step 2: After the reaction has cooled to room temperature, the product is washed by centrifugation in N,N-dimethylformamide at 7800~8200 rpm, and then dried at 60~70℃ to obtain T-ZrNs.
[0010] The invention is further characterized in that, Furthermore, zirconium salts include any one of zirconium chloride, zirconium phosphate, and zirconium nitrate.
[0011] Furthermore, carboxyl-containing polydentate ligands refer to organic compounds that contain two or more carboxyl groups (-COOH) and can form coordinate bonds with zirconium ions through the oxygen atoms of these carboxyl groups; including any one of terephthalic acid, 4,4'-biphenyldicarboxylic acid, and pyromellitic acid.
[0012] Furthermore, the acetic acid modifier is acetic acid.
[0013] Furthermore, the ratio of zirconium salt, carboxyl-containing polydentate ligand, and acetic acid modifier is 0.9 g-1.5 g: 0.6 g-1.0 g: 1 ml.
[0014] Furthermore, the ultrasonic dispersion time in step 1 is 20-30 min.
[0015] Furthermore, the centrifugal washing described in step 2 shall be performed no less than 5 times.
[0016] The second technical solution of the present invention is: zirconium nanosheets with confinement effect, prepared by the above preparation method.
[0017] The third technical solution of the present invention is the application of zirconium nanosheets with confinement effect. The T-ZrNs prepared in this invention are applied to the tanning process of goat's tanned leather, specifically as follows: 6% zirconium nanosheets are added, the initial pH is 3.0, and the solution is allowed to permeate for 120-150 minutes. Then the temperature is raised to 35-40°C, and the solution is allowed to permeate for another 120-150 minutes. 3% sodium bicarbonate is slowly added (one drop every 1-2 seconds using a dropper), for a total of three additions, with a 30-minute interval between each addition, so that the final pH rises to 4.5-5.0. After stopping the drum overnight, the drum is turned on for 30-40 minutes the next day, the drum is removed, and the drum is mounted.
[0018] In this invention, the amounts of zirconium nanosheets and sodium bicarbonate added are determined based on the mass of the tanning agent.
[0019] The beneficial effects of this invention are: This invention proposes a method to construct T-ZrNs by reacting zirconium salt, carboxyl-containing polydentate ligands, and acetic acid modifiers into DMF. When applied to leather tanning, this method utilizes spatial confinement to reduce the diffusion activation energy of zirconium ions, thereby increasing their penetration into collagen fibers and avoiding problems such as "surface over-tanning" and "core formation." This enhances the penetration of zirconium ions into leather collagen fibers, achieving better tanning results. Subsequent pH adjustment ensures that the T-ZrNs are uniformly distributed within the leather collagen fibers, exposing zirconium active sites and enabling multi-point cross-linking between these sites and the collagen fibers.
[0020] The T-ZrNs prepared in this invention can penetrate and distribute more evenly in the collagen fibers of leather than traditional zirconium salts. Furthermore, by adjusting the pH in subsequent processes, the reactive sites of zirconium can be effectively exposed, achieving multi-point cross-linking between the collagen fibers. When this T-ZrNs is applied to the tanning process of goat's hide, the shrinkage temperature of the tanned leather can reach 73 °C. Attached Figure Description
[0021] Figure 1 This is a T-ZrNsTEM image (200nm) prepared in Example 2 of this invention.
[0022] Figure 2 This is a T-ZrNsTEM image (50 nm) prepared in Example 2 of this invention. Detailed Implementation
[0023] The present invention will be further described below with reference to the accompanying drawings and specific embodiments.
[0024] Example 1 The present invention provides a method for preparing zirconium nanosheets with confinement effect, comprising the following steps: Step 1: Add 0.9 g of zirconium salt (zirconium chloride), 0.6 g of carboxyl-containing polydentate ligand (4,4'-biphenyl dicarboxylic acid), and 1 ml of acetic acid modifier to DMF (N,N-dimethylformamide). The 4,4'-biphenyl dicarboxylic acid and acetic acid are prepared in different concentration gradients (0.6 g:1 ml, 1.0 g:1 ml, 1.4 g:1 ml). Disperse the mixture ultrasonically at room temperature for 20-30 min, then transfer it to a polytetrafluoroethylene high-pressure reactor and heat it to 120 ℃-130 ℃ for 30-40 min.
[0025] Step 2: After the reaction has cooled to room temperature, the product is washed at least 5 times by centrifugation in DMF (N,N-dimethylformamide) at a speed of 7800-8200 rpm, and then dried at 60-70 ℃ to obtain T-ZrNs.
[0026] Example 2 Step 1: Add 0.9 g of zirconium salt (zirconium chloride), 0.6 g of carboxyl-containing polydentate ligand (terephthalic acid), and 1 ml of acetic acid modifier to DMF (N,N-dimethylformamide). The terephthalic acid and acetic acid are prepared in different concentration gradients (0.6 g:1 ml, 1.0 g:1 ml, 1.4 g:1 ml). Disperse the mixture ultrasonically at room temperature for 20-30 min, then transfer it to a polytetrafluoroethylene high-pressure reactor and heat it to 120 ℃-130 ℃ for 30-40 min.
[0027] Step 2: After the reaction has cooled to room temperature, the product is washed at least 5 times by centrifugation in DMF (N,N-dimethylformamide) at a speed of 7800-8200 rpm, and then dried at 60-70 ℃ to obtain T-ZrNs.
[0028] Example 3 Step 1: Add 0.9 g of zirconium salt (zirconium chloride), 0.6 g of carboxyl-containing polydentate ligand (pyromellitic acid), and 1 ml of acetic acid modifier to DMF (N,N-dimethylformamide). The pyromellitic acid and acetic acid are prepared in different concentration gradients (0.6 g:1 ml, 1.0 g:1 ml, 1.4 g:1 ml). Disperse the mixture ultrasonically at room temperature for 20-30 min, then transfer it to a polytetrafluoroethylene high-pressure reactor and heat it to 120 ℃-130 ℃ for 30-40 min.
[0029] Step 2: After the reaction has cooled to room temperature, the product is washed at least 5 times by centrifugation in DMF (N,N-dimethylformamide) at a speed of 7800-8200 rpm, and then dried at 60-70 ℃ to obtain T-ZrNs.
[0030] Example 4 Step 1: Add 1.5 g zirconium salt (zirconium chloride), 1.0 g carboxyl-containing polydentate ligand (4,4'-biphenyl dicarboxylic acid), and 1 ml acetic acid modifier to DMF (N,N-dimethylformamide). The 4,4'-biphenyl dicarboxylic acid and acetic acid are prepared in different concentration gradients (0.6 g:1 ml, 1.0 g:1 ml, 1.4 g:1 ml). Disperse the mixture ultrasonically at room temperature for 20-30 min, then transfer it to a polytetrafluoroethylene high-pressure reactor and heat it to 120 ℃-130 ℃ for 30-40 min.
[0031] Step 2: After the reaction has cooled to room temperature, the product is washed at least 5 times by centrifugation in DMF (N,N-dimethylformamide) at a speed of 7800-8200 rpm, and then dried at 60-70 ℃ to obtain T-ZrNs.
[0032] Example 5 Step 1: Add 1.5 g of zirconium salt (zirconium chloride), 1.0 g of carboxyl-containing polydentate ligand (terephthalic acid), and 1 ml of acetic acid modifier to DMF (N,N-dimethylformamide). The terephthalic acid and acetic acid are prepared in different concentration gradients (0.6 g:1 ml, 1.0 g:1 ml, 1.4 g:1 ml). Disperse the mixture ultrasonically at room temperature for 20-30 min, then transfer it to a polytetrafluoroethylene high-pressure reactor and heat it to 120 ℃-130 ℃ for 30-40 min.
[0033] Step 2: After the reaction has cooled to room temperature, the product is washed at least 5 times by centrifugation in DMF (N,N-dimethylformamide) at a speed of 7800-8200 rpm, and then dried at 60-70 ℃ to obtain T-ZrNs.
[0034] Example 6 Step 1: Add 1.5 g zirconium salt (zirconium chloride), 1.0 g carboxyl-containing polydentate ligand (pyromellitic acid), and 1 ml acetic acid modifier to DMF (N,N-dimethylformamide). The pyromellitic acid and acetic acid are prepared in different concentration gradients (0.6 g:1 ml, 1.0 g:1 ml, 1.4 g:1 ml). Disperse the mixture ultrasonically at room temperature for 20-30 min, then transfer it to a polytetrafluoroethylene high-pressure reactor and heat it to 120 ℃-130 ℃ for 30-40 min.
[0035] Step 2: After the reaction has cooled to room temperature, the product is washed at least 5 times by centrifugation in DMF (N,N-dimethylformamide) at a speed of 7800-8200 rpm, and then dried at 60-70 ℃ to obtain T-ZrNs.
[0036] Example 7 Step 1: Add 2.1 g of zirconium salt (zirconium chloride), 1.4 g of carboxyl-containing polydentate ligand (4,4'-biphenyl dicarboxylic acid), and 1 ml of acetic acid modifier to DMF (N,N-dimethylformamide). The 4,4'-biphenyl dicarboxylic acid and acetic acid are prepared in different concentration gradients (0.6 g:1 ml, 1.0 g:1 ml, 1.4 g:1 ml). Disperse the mixture ultrasonically at room temperature for 20-30 min, then transfer it to a polytetrafluoroethylene high-pressure reactor and heat it to 120 ℃-130 ℃ for 30-40 min.
[0037] Step 2: After the reaction has cooled to room temperature, the product is washed at least 5 times by centrifugation in DMF (N,N-dimethylformamide) at a speed of 7800-8200 rpm, and then dried at 60-70 ℃ to obtain T-ZrNs.
[0038] Example 8 Step 1: Add 2.1 g of zirconium salt (zirconium chloride), 1.4 g of carboxyl-containing polydentate ligand (terephthalic acid), and 1 ml of acetic acid modifier to DMF (N,N-dimethylformamide). The terephthalic acid and acetic acid are prepared in different concentration gradients (0.6 g:1 ml, 1.0 g:1 ml, 1.4 g:1 ml). Disperse the mixture ultrasonically at room temperature for 20-30 min, then transfer it to a polytetrafluoroethylene high-pressure reactor and heat it to 120 ℃-130 ℃ for 30-40 min.
[0039] Step 2: After the reaction has cooled to room temperature, the product is washed at least 5 times by centrifugation in DMF (N,N-dimethylformamide) at a speed of 7800-8200 rpm, and then dried at 60-70 ℃ to obtain T-ZrNs.
[0040] Example 9 Step 1: Add 2.1 g of zirconium salt (zirconium chloride), 1.4 g of a series of carboxyl-containing polydentate ligands (pyromellitic acid), and 1 ml of acetic acid modifier to DMF (N,N-dimethylformamide). Pyromellitic acid and acetic acid are prepared in different concentration gradients (0.6 g:1 ml, 1.0 g:1 ml, 1.4 g:1 ml). Disperse the mixture ultrasonically at room temperature for 20-30 min, then transfer it to a polytetrafluoroethylene high-pressure reactor and heat it to 120 ℃-130 ℃ for 30-40 min.
[0041] Step 2: After the reaction has cooled to room temperature, the product is washed at least 5 times by centrifugation in DMF (N,N-dimethylformamide) at a speed of 7800-8200 rpm, and then dried at 60-70 ℃ to obtain T-ZrNs.
[0042] Key innovations of this invention: This invention proposes a T-ZrNs synthesized using a "pseudo-assembly-disassembly" mechanism, the specific process of which is as follows: Pseudo-assembly stage: In the initial stage of the reaction, acetic acid preferentially coordinates with zirconium ions to form a three-dimensional bulk intermediate. Acetic acid occupies interlayer coordination sites, weakening interlayer interactions.
[0043] Disassembly stage: As the reaction proceeds, a series of carboxyl-containing polydentate ligands gradually compete to replace acetic acid, and the unstable three-dimensional structure begins to dissociate from the outer surface, eventually forming T-ZrNs.
[0044] like Figure 1 and Figure 2 The image shows a TEM image of T-ZrNs. As can be seen from the image, T-ZrNs exhibit a sheet-like structure with individual sizes ranging from 50 to 100 nm. When applied to the tanning process of goat's sour leather, the shrinkage temperature of the tanned leather can be increased from 43 ℃ to 73 ℃ without the "core formation" phenomenon.
[0045] The above embodiments and specific parameters are only for clearly illustrating the verification process of the invention and are not intended to limit the scope of patent protection of the present invention. The scope of patent protection of the present invention shall still be determined by its claims. Similarly, any equivalent structural changes made based on the description and drawings of the present invention shall also be included within the scope of protection of the present invention.
Claims
1. A method for preparing zirconium nanosheets with confinement effect, characterized in that, A series of zirconium salts, a series of carboxyl-containing polydentate ligands, and an acetic acid modifier were dissolved in N,N-dimethylformamide, ultrasonically dispersed, and then transferred to a reaction vessel for heating and reaction to obtain T-ZrNs.
2. The method for preparing zirconium nanosheets with confinement effect according to claim 1, characterized in that, The specific operating steps are as follows: Step 1: Add zirconium salt, carboxyl-containing polydentate ligand, and acetic acid modifier to N,N-dimethylformamide, wherein the ratio of the series of carboxyl-containing polydentate ligands to acetic acid modifier is 0.6g~1.4g:1ml. Disperse the mixture by ultrasonication at room temperature, transfer it to a polytetrafluoroethylene high-pressure reactor, heat it to 120℃~130℃, and react for 30~40min. Step 2: After the reaction has cooled to room temperature, the product is washed by centrifugation in N,N-dimethylformamide at 7800~8200 rpm, and then dried at 60~70℃ to obtain T-ZrNs.
3. The method for preparing zirconium nanosheets with confinement effect according to claim 2, characterized in that, The zirconium salt includes any one of zirconium chloride, zirconium phosphate, and zirconium nitrate.
4. The method for preparing zirconium nanosheets with confinement effect according to claim 2, characterized in that, The carboxyl-containing polydentate ligand refers to an organic compound containing two or more carboxyl groups (-COOH) in its molecule, which can form coordinate bonds with zirconium ions through the oxygen atoms of these carboxyl groups; including any one of terephthalic acid, 4,4'-biphenyl dicarboxylic acid, and pyromellitic acid.
5. The method for preparing zirconium nanosheets with confinement effect according to claim 2, characterized in that, The acetic acid modifier is acetic acid.
6. The method for preparing zirconium nanosheets with confinement effect according to claim 2, characterized in that, The ratio of zirconium salt, carboxyl-containing polydentate ligand, and acetic acid modifier is 0.9 g-1.5 g: 0.6 g-1.0 g: 1 ml.
7. The method for preparing zirconium nanosheets with confinement effect according to claim 2, characterized in that, The ultrasonic dispersion time in step 1 is 20-30 min.
8. The method for preparing zirconium nanosheets with confinement effect according to claim 2, characterized in that, The centrifugal washing described in step 2 shall be performed no less than 5 times.
9. Zirconium nanosheets exhibiting confinement effect, characterized in that, The zirconium nanosheets with confinement effect were prepared using the method described in any one of claims 1-8.
10. The application of zirconium nanosheets with confinement effect, characterized in that, T-ZrNs was applied to the tanning of pickled goatskin. 6% zirconium nanosheets were added, with an initial pH of 3.
0. The mixture was allowed to penetrate for 120-150 minutes, then the temperature was raised to 35-40°C, and penetration continued for another 120-150 minutes. 3% sodium bicarbonate was slowly added three times, with 30-minute intervals between each addition, until the final pH reached 4.5-5.
0. After stopping the drum overnight, the drum was turned on for 30-40 minutes the next day, removed from the drum, and mounted.